Paleobiological Methods for Studying the History of Early Anthropogenes in Fergana (Texas Journal of Philology, Culture and History, 2023)
The article presents some results of the reconstruction of the paleogeographic development of nature during the late Cenozoic, a geological stage that is closely connected with the history of the formation of man as an anthropological type on the territory of the northern slopes of High Asia and the Fergana region in particular. An integral component of paleogeographic research is "biogeocenosis", which includes a natural complex representing the totality of flora and fauna - "biocenosis". Paleontological sources characterizing the rate of evolution of biogeographical transformations were identified as a result of paleogeographical study of cultural horizons at the historical monuments of the early anthropogen Selungur, Sokh, Chashma, Obzhaz and a newly discovered complex of objects in the eastern part of the Fergana region - Khanobad. Based on the paleogeographic study, the stages of the history of the evolutionary formation of nature, against which the development of the most ancient cultures of mankind took place, are detailed. The research results are a modest addition to the construction of the regional chronostratigraphic scale of the Late Cenozoic on the territory of the northern slopes of High Asia